Bony orbital form in two groups of Catarrhini primates: how asymmetrical are they? - Pere M. Parés-Casanova (Annals of Tropical Research, 2025)
The aim of this study was to compare left and right osseous orbit forms in two different Catarrhini primate genera using geometric morphometric techniques. The analysis was carried out on 20 well-preserved skulls from gorilla (Gorilla gorilla, n=10) and papios (drill [Mandrillus leucophaeus, n=3] and mandrill [M. sphinx, n=7]) from animals kept in a zoo, which were photographed in their frontal norm. A set of 4 sagittal landmarks on the face and 23 semilandmarks on each orbit contour were used. According to the results, the right and left orbitas were similar in size but not in shape, appearing to be significant for individual-by-side interaction (fluctuating asymmetry). This may be due to a developmental instability due to life in captivity. Fluctuating asymmetry was clearly higher among gorillas, seeming logical as hominoidea primates suffer stress in captivity more than cercopithecidae (papios and mandrills). Side directional differences were significant only for papios. We suggest this is due to a stronger stroke of lateralized mastication compared to gorillas as the mandibles of papios are longer.